The Effect of Socialization on Community Participation in Vaccination against Covid-19 in East Cilandak Village - Syamsiah Badruddin; Mita Maya Meysyanti (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2022)
Socialization is a process where individuals will learn many things about life before entering the wider community. The first agent of socialization is parents or family. Parents are the first to teach individuals to interact well. When an individual already has enough knowledge about the life of the wider community and can also behave when interacting with other people, it means that the individual has been able to enter into social life. Socialization can be very influential on individual actions if the motivating factor for individuals to take these actions is very large. This paper wants to see how much influence the socialization has on community participation in vaccinating Covid-19 in the East Cilandak sub-district. The purpose of this study was to analyze how much influence socialization had on community participation in the Covid-19 vaccination in the East Cilandak sub-district. This study uses quantitative methods. The research data was obtained from distributing questionnaires to the people who live in the East Cilandak sub-district. Based on data analysis using SPPP, it was concluded that there was a positive or significant effect between socialization and community participation in vaccinating Covid-19 in the East Cilandak sub-district.